Development of directly grown‐graphene–silicon Schottky barrier solar cell using co‐doping technique. (6th April 2022) - Rehman, Malik Abdul; Park, Sewon; Khan, Muhammad Farooq; Bhopal, Muhammad Fahad; Nazir, Ghazanfar; Kim, Minjae; Farooq, Ayesha; Ha, Jisang; Rehman, Shania; Jun, Seong Chan; Park, Hyung‐Ho
Summary: Low‐cost, highly efficient, and low‐power devices are essential for energy harvesting applications. Despite numerous studies having been conducted on transferable graphene solar cells, large‐area growth and long‐term stability continue to remain elusive, which limits the practicability of graphene‐based photovoltaic devices. Plasma‐enhanced chemical vapor deposition is a promising, efficient, and facile method for synthesizing graphene over a large area without the use of a metal catalyst, but defects formed during graphene growth adversely affect the power conversion efficiency (PCE) of graphene/Si solar cells in which the graphene is used. In this work, we successfully employed acid‐based graphene‐Si macromolecular photovoltaic devices chemically doped with polymeric perfluorinated sulfonic acid (PFSA) macromolecules and nitric acid (HNO3 ). We achieved an improved PCE of about 9.27% with PFSA doping compared with the value (7.64%) without PFSA doping, and it increased substantially to 10.44% after co‐doping with HNO3 . PFSA macromolecular doping also led to a substantial increase in the carrier concentration, which helped to reduce the sheet resistance of graphene and improved the work function of the device. In particular, the synergistic effect of co‐doping with HNO3 helped to improve the number of active sites and charge separation. Along with the increase in carrier concentration, doping with PFSA reduced the number of defects, resulting in the graphene having a smooth and uniform surface, which effectively increased the open‐circuit voltage ( V oc ) from 0.500 to 0.521 V. We surmise that nonvolatile PFSA macromolecular and volatile HNO3 co‐doping has high potential for use in the fabrication of low‐cost directly grown‐graphene‐based photovoltaic devices. Highlights: Plasma‐enhanced chemical vapor deposition technique used for the direct growth of graphene without metal catalyst. Naturally grown oxide thickness optimized. Nonvolatile macromolecular dopant per‐fluorinated polymeric sulfonic acid (PFSA) and volatile nitric acid (HNO3 ) were used for direct growth graphene doping. The power conversion efficiency of ~9.27% with PFSA doping from 7.64%; further, its substantial increase up to 10.44% after co‐doping with HNO3 were achieved with long‐term stability. Abstract : The CVD grown graphene on metal catalyst is mostly used for the fabrication of graphene solar cell which requires complex wet transfer process and limited scalability of device. However, by using PECVD we have grown directly on any insulating surface with large active area and co‐doping with uniform inter oxide layer can significantly improve the performance.